Envisioning a Dystopian, Post-Christian Society in P. Anderson Graham’s The Collapse of Homo Sapiens - Hale, Frederick (Religion & theology, 2021)
Abstract As one of many contemporary British dystopian novels, P. Anderson Graham’s 1923 The Collapse of Homo Sapiens envisaged Britain in the twenty-second century as a devastated society that has largely reverted to a primitive, non-Christian state. However, a remnant of the surviving population has memories of the religious dimensions of national life, helping them to cope with the exigencies of their meagre existence. A modest revival of the faith of their forebears ensues, which in turn triggers a reaction against the re-assertion of Christianity by nationalistic elements that regard it as too charitable a social force to fortify their efforts to revitalise British culture in a hostile geopolitical setting. The narrative perspective of the novel is critical of the truncated state of that religion in Britain in the 1920s and how this was failing to guide and inspire peoples’ lives at that time.